2021
DOI: 10.1016/j.aprim.2021.102102
|View full text |Cite
|
Sign up to set email alerts
|

Implantación de una prueba rápida de infección estreptocócica: ¿su uso también mejora la adherencia antibiótica?

Abstract: Objetivo Evaluar la influencia del resultado de la prueba rápida de diagnóstico para la identificación del antígeno estreptocócico en infecciones faringoamigdalares pediátricas, en términos de mejora de la adherencia a la terapia antibiótica. Diseño Ensayo clínico comunitario de dos grupos de estudio con asignación aleatoria. Emplazamiento Centros de atención primaria de Cataluña Central. Participantes En el estudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Using a rapid strep test alongside the Centor Criteria for diagnosing group A betahemolytic Streptococcus pharyngitis can prevent unnecessary antibiotic prescriptions [36], thus proving convenient and acceptable to both patients and clinicians while preventing economic damage [37]. Despite recommendations advocating the avoidance of blood test performance, our study revealed that merely 19.7% of tonsillitis cases underwent a rapid strep test.…”
Section: Discussionmentioning
confidence: 76%
“…Using a rapid strep test alongside the Centor Criteria for diagnosing group A betahemolytic Streptococcus pharyngitis can prevent unnecessary antibiotic prescriptions [36], thus proving convenient and acceptable to both patients and clinicians while preventing economic damage [37]. Despite recommendations advocating the avoidance of blood test performance, our study revealed that merely 19.7% of tonsillitis cases underwent a rapid strep test.…”
Section: Discussionmentioning
confidence: 76%